ChemInform Abstract: Regio‐ and Stereospecific Synthesis of C‐3 Functionalized Proline Derivatives by Palladium Catalyzed Directed C(sp3)—H Arylation. Issue 12 (March 2015) - Affron, Dominic P.; Davis, Owen A.; Bull, James A.
Abstract Pd‐catalyzed C—H functionalization stereospecifically installs hetero‐aryl and vinyl substituents at the unactivated 3‐position of proline derivatives.